A Deep Dive into the Emotional, Spiritual, and Socio-Religious Dimensions of Syair Soenoer - Yulia, Novi; Andoni, Yudhi (Jurnal Ceteris Paribus, 2025)
The emotional expression found within Syair Soenoer is not a simple sentiment but a profound and agonized representation of a soul caught in the crucible of a civilization-defining conflict. It articulates a deeply personal crisis that mirrors the larger schism tearing apart Minangkabau society in the early 19th century. The poem’s central figure is one who experiences a radical rupture with his past, his community, and his own inherited identity. This rupture is described through potent imagery of flight and exile, where the protagonist flees from the familiar landscapes of his youth— the "pantai yang lama" (old shore), the "malam yang dulu" (nights of old), and the "rumah nan basandi adat" (house built according to custom). These images are not merely nostalgic; they are the very foundations of his being, and his departure from them signifies a severing of roots. The act of leaving is imbued with a sense of finality and sorrow, suggesting an emotional state of profound loss and displacement. He does not leave wistfully; he leaves with such urgency that he does not even turn back, a gesture that underscores the trauma and desperation driving him away.